2010
DOI: 10.1088/0967-3334/31/7/n01
|View full text |Cite
|
Sign up to set email alerts
|

Cuff width alters the amplitude envelope of wrist cuff pressure pulse waveforms

Abstract: The accuracy of noninvasive blood pressure (BP) measurement with any method is affected by cuff width. Measurement with a too narrow cuff overestimates BP and measurement with a too wide cuff underestimates BP. Automatic wrist cuff BP monitors use permanently attached narrow cuffs with bladders about 6 cm wide. Such narrow cuffs should result in under-cuffing for wrist circumferences larger than 15 cm. The objective of this qualitative study was to show that a narrow wrist cuff results in increased BP values w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…For example, cuff width for 20 cm wrist circumference is 8 cm. Our previous study [10] showed the effect of under-cuffing on accuracy and reliability of wrist cuff BP devices. Investigators interested in wrist cuff BP determination should take this into account.…”
Section: Discussionmentioning
confidence: 99%
“…For example, cuff width for 20 cm wrist circumference is 8 cm. Our previous study [10] showed the effect of under-cuffing on accuracy and reliability of wrist cuff BP devices. Investigators interested in wrist cuff BP determination should take this into account.…”
Section: Discussionmentioning
confidence: 99%
“…The cuff size influences the accuracy of noninvasive BP measurement not only in brachial, but in wrist [11], or even in toe BP measurements [12]. As the cuff size may result in differences between peripheral and central BP readings [13], the cuff size should be selected correctly for noninvasive central BP measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Besides aiding in making observations on regulation mechanisms, the large number of studies has also contributed to identifying technology requirements for measurement of arterial properties. Device characteristics such as PPG sensor contact impact on PTT [ 65 ], hydrostatic effects [ 66 ], BP cuff size/shape/design properties [ 67 , 68 , 69 ], different cuff inflation strategies [ 60 , 70 ], and measurement of cardiac factors [ 71 ] have been investigated, and processes for validating devices have been improved [ 66 ]. Motion artifacts and signal-to-noise ratio have also been thoroughly investigated [ 72 ].…”
Section: More Advanced Assessment Of the Vascular Propertiesmentioning
confidence: 99%
“…In addition to this, many sensor effects are not fully understood or characterized. PPG contact pressure, cuff size and placement, and wrapping tightness have recently been found to affect signal quality and interpretability [ 65 , 67 , 68 , 69 , 72 ]. In certain cases, even sensor effects of invasive measures such as arterial lines can make the data unusable (e.g., inaccurate damping).…”
Section: Data-driven Approachesmentioning
confidence: 99%